An exploratory study on the information needs and information seeking behavior of selected construction workers in Quezon City - Laurora, Marvic R.; Santos, Yhna Therese P. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2022)
Information is an invaluable and essential commodity in every people’s lives. People need information to develop their fullest potentials and skills by means of educating and equipping themselves with the proper knowledge and new learnings they acquire to become more successful in their job roles; to enrich their skills, and improve their quality of life. Construction workers offer their services by means of manual physical labor. Oftentimes, they are marginalized and underserved due to their illiteracy and as they term it, “no read, no write” making them vulnerable to be trapped in poverty. However, despite being under these circumstances, construction workers seek for valuable information pertaining to their job roles as they seek for career growth and self-improvement. They aim to prosper and excel in their line of work and improve their status in life, hence the need for them to find better employment opportunities offering higher salaries and wages or companies offering permanent employment and better benefits to workers like them, in spite of their age, education background or marital status.

Studying this underserved sector brought light on the topics that posed interests to this group. These were the topics about or relevant to working in the construction industry, finding a better opportunity, or becoming more educated through informal channels of information. Having said that, this study sought to determine the information needs and the information-seeking behavior of selected construction workers in Quezon City particularly, the motivating factors that paved the way to their information search along with the hurdles faced by the construction workers in seeking information. The study utilized mixed research methods through survey methodology and focus group discussions for collecting data. The findings revealed the construction workers were interested in topics that can help them improve their quality of life. Employment topics, personal development, and external environment play key motivating factors in their information-seeking endeavors. It is evident that the respondents barely had time left for them to search for information as reflected by the frequency of accessing information which is a minimum of one to two times and maximum of five times per week only. An easy and quick access to finding information is most preferred by this group, either by personally asking, or chatting through Facebook messenger, or sending a short message (text message) to other people whom they believe they are comfortable with, people whom they trust or people whom they thought have more knowledge on their subject of their interest, in the persona of their colleagues, bosses, neighbors, friends and other peers. Searching information on the internet was also favored by the respondents. Formal sources of information were demonstrated to be least consulted by the respondents. A happy and positive disposition during the information search process were embodied by most of the respondents which can be explained by the ISP method, or the Information Search Process postulated by Carol Kuhltau (1999).

The challenges in the information search were strongly tied to the physical and mental stress they encounter after their daily shifts at work. The respondents shared that they would rather rest than seek for information, to prepare for another heavy and tiring work the next day. Moreover, another barrier of information was when the respondents were relocated to remote construction sites where there was a limited or no internet connection. Lack of proper education is another factor which made it difficult for this group of workers to seek for information. Lastly, being consumed at work provided little or no time to seek for information, which proved to be the one of the biggest challenges in the information seeking process of the construction workers.
Thesis
Keywords: Construction workers -- Philippines -- Quezon City